PENENTUAN JENIS MEDIA TERHADAP EFEKTIVITAS PERTUMBUHAN JAMUR TRICHODERMA HARZIANUM - Riani, Pevi; Futeri, Renny (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2023)
This study aims to determine a suitable medium for the growth Trichoderma harzianum. The treatments tested were rice media (M1), bran media (M2), corn media (M3), potato media (M4), and rice husk mixed media (M5). The parameters observed in this study were the quality test of conidia density using a microscope and haemacytometer, macroscopic observation of the media for 7 days and microscopic observation of the media to evaluate the media that had the best effectiveness as a medium for propagation of Trichoderma harzianum. The initial isolate of Trichoderma harzianum used had a conidia density of 2,9x109conidia/ml. The results showed that the propagation of Trichoderma harzianum in various media affected the macroscopic, microscopic and conidia density changes of Trichoderma harzianum. Trichoderma harzianum can grow on all treatment media. The bran media is the medium with the highest conidia density compared to other media.